Perilaku Bullying Pada Remaja Ditinjau Dari Self Esteem Dan Jenis Kelamin - Mulachela, Zainab Husin; , Dra. Juliani Prasetyaningrum, M. Si., Psi (2017)
This reasearch aims to know correlation between bullying behavior in students with self esteem, and to show the difference in behavior of bullying be reviewed from gender. This research was conducted in one of the first high school in the city of Surakarta. The subject in this research amounts 100 people consisting of 50 students are male and 50 students are female. Sampling is done with cluster random sampling techniques. The methods used in this research is quantitative methods with a measuring instrument in the form of bullying behavior scale and self esteem. Technique of data analysis with correlation Product Moment from Pearson and analysis using t-test. Based on the results of data analysis with the correlation product moment obtained coefisien correlation (rxy) =-0.292 with significance = 0.002 (p < 0.01) it means there is a negative correlations between self esteem with bullying behavior on students. Bullying behaviour variables included in the low categories, while self esteem variable include in a hingh categories. In addition to that of the test results with either using independent samples t-test obtained the values test-t is t = 2.841 either coefisien value sig = 0.005 (p < 0.05) it means there is a difference bullying behaviour between male students and female students. Reasearch shows that male students more often do bullying behaviour than female students.